Presumed Optic Neuropathy Secondary to Intranasal Cocaine Use: A Case Report - Joseph, Jasmine (Canadian Journal of Optometry, 2023)
Ocular side effects of intranasal cocaine use are rare but can include corneal epithelial changes, retinal vascular complications, and orbital inflammation.1 This case report describes a 54-year-old Black female who was a habitual cocaine user and presented with acute, painless vision loss of the right eye and right optic disc edema. Cocaine’s sympathomimetic properties can lead to optic neuropathy; therefore, a patient’s social history of recreational drug use should not be dismissed when considering potential etiologies.